Hormone replacement therapy and prevention of chronic conditions. (4th May 2019) - Gambacciani, M.; Cagnacci, A.; Lello, S.
Abstract: Nowadays, postmenopausal women are largely undertreated. Analysis of conflicting results among different studies suggests that hormone replacement therapy (HRT) can prevent osteoporosis and cardiovascular disease in symptomatic, early postmenopausal women. In fact, climacteric symptoms are related to an increased risk of chronic conditions, including hypertension and cardiovascular disease. Different scientific societies have pointed out that patient selection, timing of initiation, and the choice of the type and dose of HRT used are the major determinants of the ultimate effect of HRT on women's health and quality of life in selected women. HRT may prevent chronic conditions when started in symptomatic women before the age of 60 years or within 10 years of the onset of the menopause, taking into consideration the characteristics and risk profiles of each given woman. The bulk of scientific evidence from preclinical, clinical, epidemiological, and also randomized studies indicates that wisely selected HRT is generally useful and rarely dangerous. Following simple and well-established rules, HRT benefits outweigh all of the possible risks. Progestogen choice can make the difference in terms of cardiovascular disease benefits.